Secondary Productivity of Crambidae Family in Cigambreng River, Tapos Village, Bogor: Produktivitas Sekunder Famili Crambidae di Sungai Cigambreng, Desa Tapos, Bogor - Arif Nurcahyanto; Ahyar Pulungan; Didit Abdillah; Muhammad Irfan Afif; Grin Tommy Panggabean; Rizky Regina Kawirian; Chichilia Qaila Azzahra Rahman; Majariana Krisanti (Tropical Fisheries Management Journal, 2020)
Secondary productivity is the formation of biomass of heterotrophic organisms in units of time including biomass that is lost in a certain time unit. The Crambidae family is an insect that has aquatic larvae and will become an air insect after the larval phase. This species has the potential to become a pest for agriculture. The study was conducted in October 2019 for one month. The Crambidae family species found consists of two species, Petrophila sp. and Elophila sp. The abundance of Crambidae during the study ranged from 100 ind/m2 to 422 ind/m2. Secondary productivity was analyzed by the size frequency method. The secondary productivity of the Crambidae family in Cigambreng river waters for one month was 47.7915 g/m2/month, the biomass formed was 14.9669 g/m2 and the P/B ratio was 3.1931.